Sulfone-based deep blue thermally activated delayed fluorescence emitters: solution-processed organic light-emitting diodes with high efficiency and brightness - Jürgensen, Nils; Kretzschmar, Andreas; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry of materials, 2017)
Low efficiencies of soluble blue emitter materials remain a major issue in the development of printed organic light-emitting devices. n-Alkylated carbazoles or sterically demanding ortho-substituted diphenylamines were employed as donor elements to increase solubility and to preserve blue emission of thermally activated delayed fluorescence (TADF) donor-acceptor-donor emitters employing a p-bis(phenylsulfonyl)benzene acceptor described in the literature. The soluble molecules exhibited increased steric hindrance of the amine donors and a small ΔEST as low as 0.32 eV. Thermally activated delayed fluorescence occurs, and photoluminescence quantum yields of ≤82% were achieved. Application of these TADF molecules in solution-processed organic light-emitting diodes resulted in high brightnesses of ≤10000 cd/m2, current efficiencies of ≤9.5 cd/A, and external quantum efficiencies of ≤8.5%, while retaining deep blue emission ranging from 466 to 436 nm with color coordinates low as CIEy = 0.08.